2001
DOI: 10.1046/j.1365-2036.2001.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cytochrome P‐450‐dependent liver activity in cirrhotic patients with Helicobacter pylori infection

Abstract: Background: Helicobacter pylori gastric infection has been associated with various digestive and extra‐digestive diseases. The systemic influence of gastric H. pylori infection seems to be mediated by the release of various cytokines. In liver disease, bacterial infections have been associated with the impairment of liver metabolic function. Aims: To evaluate the influence of H. pylori infection on liver function as assessed by means of the monoethylglycinexylidide test, which depends upon liver blood flow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…This finding underscores that the minimal modifications in CYP-450 activity that occurred during treatment are completely reversible. Furthermore, since it is unlikely that H. pylori eradication may lead to an improvement in gastric emptying and/or increased absorption of aminopyrine (38)(39)(40), it should be interesting to evaluate in larger cohorts of patients whether H. pylori may affect CYP-450 activity as seems to happen in patients with chronic liver disease (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores that the minimal modifications in CYP-450 activity that occurred during treatment are completely reversible. Furthermore, since it is unlikely that H. pylori eradication may lead to an improvement in gastric emptying and/or increased absorption of aminopyrine (38)(39)(40), it should be interesting to evaluate in larger cohorts of patients whether H. pylori may affect CYP-450 activity as seems to happen in patients with chronic liver disease (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase is a key enzyme in sex steroid biosynthesis, being responsible for conversion of C19 steroids to estrogens in a number of human tissues, including the liver (12,13). As some researchers have recently found that H. pylori infection selectively affects cytochrome P-450 liver activity (14), it is plausible that H. pylori-infected patients show diminished rates of conversion of steroids to estrogens. These researchers, however, did not differentiate CagA-seropositive and -seronegative patients; therefore, their findings cannot be applied tout course to our results, which showed that only CagA-seropositive osteoporotic patients had reduced systemic levels of estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the exact mechanism of H. pylori endotoxins on different hepatic lesions is not known. In cirrhotic patients, H. pylori infection seems to affect cytochrome P450 liver activity selectively 35 . Helicobacter pylori LPS can provoke a microvascular inflammatory response and permeability in the rat cardiac, renal, hepatic and pulmonary tissues, actions mediated through the activation of the inducible nitric oxide synthase isoenzyme 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In cirrhotic patients, H. pylori infection seems to affect cytochrome P450 liver activity selectively. 35 Helicobacter pylori LPS can provoke a microvascular inflammatory response and permeability in the rat cardiac, renal, hepatic and pulmonary tissues, actions mediated through the activation of the inducible nitric oxide synthase isoenzyme. 36 Thus, there is a potential capacity of H. pylori to damage the liver by producing toxins with a granulating effect on liver cell lines which, in vivo, through the portal tract, might reach the liver, thus causing hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%